Facilitating translation in biotech entrepreneurship: evaluating novel training programs in commercialization for scientist-entrepreneurs - Hisham, Farah; Nik Yusuf (Journal of Commercial Biotechnology, 2024)
The present research aims to assess the influence of green innovative behavior, technological capabilities, and university support on bio-entrepreneurship development in the Canadian context. The study also considered the bio-entrepreneurship training of students as mediators. Through the disbursement of questionnaire, the researcher collected data from the target audience. 246 questionnaires were analyzed through SPSS and AMOS. Results depicted those technological skills and green innovative behavior significantly influences BET, whereas the other direct associations have been resulted to be insignificant. But the mediation of bio-entrepreneurship training has been found to be insignificant among all hypothesized mediation associations. The present research holds various theoretical and practical implications. The research extends the growing body of literature regarding bio-entrepreneurship education on skill development in Canada. Practically, the study holds valuable implications for various stakeholders to boast skill development through bio-entrepreneurial education. The research limitations and future research indications have also been addressed in the study.